AB0960 RELATIONSHIP BETWEEN THE CAREGIVER BURDEN AND UPPER LIMB-NECK DISABILITY AND PAIN IN BABY CAREGIVERS. (2nd June 2020) - Aydin, G.; Demirel, A.; Bulut, N.; Karaduman, A. A.; Serel Arslan, S.; Yilmaz, Ö.; Gürbüz, İ.
Abstract : Background: Although caregiving is a normal part of being a parent of a young child, it is still unclear whether caregiving causes upper limb or neck disability in the caregiver. Objectives: The aim of this study was to investigate the relationship between caregiver burden and upper limb-neck disabilities and pain in baby caregivers. Methods: Sixty caregivers who are responsible for the caregiving of a 0-2 year old healthy baby, were included in this study. Physical characteristics and the gender of the caregivers were recorded. Caregiver burden was assessed by the Zarit Burden Interview; upper limb problems by DASH and neck problems by the Neck Disability Index and Neck Bournemouth Questionnaire. In addition, pain severity related to neck and upper limb was evaluated by using Visual Analog Scale over a 10 level scale. Results: The mean age of the caregivers was 30.96 ± 6.43 year. The mean body mass index of the caregivers was 23.34 ± 3.29 indicating normal body composition. Height and weight were 163.75 ± 6.01 and 62.55 ± 8.98, respectively. Ninety-five percent of the caregivers were mother and the others were the babysitter. A weak relationship was determined between the Zarit Burden Interview and DASH (p=0.02, r=0.2), while no relationship was found between caregiver burden and other assessments. Caregivers were found to have very low pain severity in the upper limb and neck. Conclusion: It has been previously reported that caregiving for a disabled child or adult causes care burden and various musculoskeletal disorders 1-4 . Current study demonstrated that giving care for a healthy child did not create care burden, and caused lower levels of pain in the upper limb and neck. References: [1]Santos, M. T. B. R., Biancardi, M., Guare, R. O., & Jardim, J. R. (2010). Caries prevalence in patients with cerebral palsy and the burden of caring for them. Special Care in Dentistry, 30 (5), 206-210. [2]Sharan, D., Ajeesh, P. S., Rameshkumar, R., & Manjula, M. (2012). Musculoskeletal disorders in caregivers of children with cerebral palsy following a multilevel surgery. Work, 41 (Supplement 1), 1891-1895. [3]Akosile, C. O., Okoye, E. C., Adegoke, B. O. A., Mbada, C. E., Maruf, F. A., & Okeke, I. A. (2013). Burden, health and quality of life of Nigerian stroke caregivers. Health Care Current Reviews, 1 (1), 105. [4]Darragh, A. R., Sommerich, C. M., Lavender, S. A., Tanner, K. J., Vogel, K., & Campo, M. (2015). Musculoskeletal discomfort, physical demand, and caregiving activities in informal caregivers. Journal of Applied Gerontology, 34 (6), 734-760. Disclosure of Interests: None declared